A regional scale 3D-model of the Skellefte mining district, northern Sweden - Bauer, Tobias; Skyttä, Pietari; Tavakoli, Saman; Hermansson, Tobias; Dehghannejad, Mahdieh; Juanatey, Maria Garcia; Weihed, Pär; Allen, Rodney; Juhlin, Christopher (Luleå tekniska universitet, Geovetenskap och miljöteknik, 2013)
Godkänd; 2013; 20131106 (tobbau)